Influence of Balance on the Quality of Life of People with Down Syndrome in School and Adult Ages: A Literature Review - Gámez-Calvo, Luisa; Gamonales, José Martín; León, Kiko; Muñoz-Jiménez, Jesús (MHSalud: Revista en Ciencias del Movimiento Humano y Salud, 2021)
The study aims to conduct a bibliographic and structured review based on the results found around the influence of balance on the quality of life of people with Down Syndrome (DS) in school and adult ages. For references searching, the following keywords were used as descriptors: “Down Syndrome,” “Balance,” and “Quality of life.” The words were always introduced in English and computerized databases; SCOPUS, WOS, and SPORTDiscus were used. Four inclusion criteria were introduced to limit the search: i) mentioning the influence of balance on the QOL of people with DS, ii) taking exclusively into consideration scientific articles, iii) having access to the full text or abstract, and iv) being written in English, Portuguese, or Spanish. In conclusion, the documents about the influence of balance in people with Down Syndrome address different research topics. Of the thirty-four articles located in the first search, seven of them meet the inclusion criteria. The reviewed scientific literature shows that the practice of physical exercise and specific training produce improvements in balance and the quality of life of people with Down syndrome, which allows establishing the recommendation to specifically train balance during physical activity sessions since there is evidence of positive effects for this group.